Effect of Agitation to Hydrocarbon Degradation by a Hydrocarbonoclastic Bacterium isolated from Chevron Pacific Indonesia’s Waste Tank in Petapahan, Riau - Irda Sayuti (International Journal of Ecophysiology, 2019)
Oxygen content is a limiting factor in the process of hydrocarbon compounds degradation by hydrocarbonoclastic bacteria. Oxygen may be supplied through agitation (stirring) during fermentation process by hydrocarbonoclastic bacteria. This study aims to to determine the optimal agitation speed for batch fermentation process by hydrocarbonoclastic bacteria isolated from the waste tank of PT Chevron Pacific Indonesia (CPI) Petapahan, Riau. This study was conducted in Biota laboratory, Universitas Andalas, West Sumatra, Indonesia. Hydrocarbonoclastic bacteria were recovered from waste samples by culturing into nutrient broth. Three different agitation speed viz. 110, 120, and 130 rpm were selected as optimization factors. The results show that the percentage of total petroleum hydrocarbon (TPH) degradation are 79.72, 87.49, and 88.35 for 110, 120, and 130 rpm, respectively. Meanwhile, chemical oxygen demand (COD) monitored during fermentation are 88.48, 90.06, and 90.16%, respectively. The agitation speed of 130 rpm is then designated as optimum factor for hydrocarbon degradation by hydrocarbonoclastic bacteria.